Subclinical mastitis in dairy cows: somatic cell counts and associated bacteria in Mymensingh, Bangladesh - Sumon, SMMR; Ehsan, MA; Islam, MT (Journal of the Bangladesh Agricultural University, 2017)
Subclinical mastitis is an economically important disease of dairy cows and has a prominent place amongst the factors that limit milk production. This study was undertaken to determine the association of somatic cell counts (SCC) and occurrence of bacteria with SCM in smallholder dairy cows in Mymensingh, Bangladesh. A total number of 240 quarters milk samples from apparently healthy lactating cows were subjected to SCC using NucleoCounter® SCC-100 ™ (Chemo Metec). A quarter was considered SCM positive if the quarter had SCC>100 x 103 cells/ml. All subclinical mastitis positive quarter milk samples were subjected to bacteriological examination and isolates were classified into major, minor, uncommon and mixed pathogens. The overall quarter-level prevalence of subclinical mastitis of dairy cows in Mymensingh district was 25% (95% CI, 19.52% to 30.48%). The most frequently isolated bacterial species were Staphylococcus aureus (18.33%) followed by coagulase-negative staphylococci (10%), Enterobacter spp. (6.67%), Escherichia coli (5%), Bacillus spp. (5%) and Pseudomonas aeruginosa (5%). Different bacterial isolates were associated with 90% cases of subclinical mastitis as mono infections or mixed infections. Mono and mixed infections significantly influenced SCC and were the most prominent factors responsible for increasing SCC. Mean SCC was the highest for Bacillus spp. (713.67 x 103 cells/ml) followed by Enterobacter spp. (395.75 x 103 cells/ml), Escherichia coli (386.00 x 103 cells/ml), Staphylococcus aureus (373.82 x 103 cells/ml), coagulase-negative staphylococci (182.67 x 103 cells/ml) and Pseudomonas aeruginosa (138.67 x 103 cells/ml). Major pathogens induced higher SCC (380.72 x 103cells/ml) than minor and other pathogen groups. J. Bangladesh Agril. Univ. 15(2): 266-271, December 2017